APPLICATION OF TYPE COOPERATIVE LEARNING MODEL JIGSAW TO IMPROVE STUDENTS 'LEARNING RESULTS IN CLASS VII SMPN 1 BATAK BRAK (INSODED Journal (International Social and Education Journal), 2019)
The purpose of this study is to research improve student social studies learning outcomes in Class VII SMPN 1 Batu Brak by applying type cooperative learning models jigsaw. This research is a classroom action research (CAR) conducted in two cycles. Each cycle consists of 4 stages, namely: planning, implementing actions, observing, and reflecting. The subjects of the study were the teachers and students of Social Sciences Class VII in SMPN1 Batu Brak Kec. Batu Brak, West Lampung in 2019/2020 Academic Year with 26 students. Data collection techniques used were using tests and observations. The data analysis technique uses the constant comparative method. The results showed that in the first cycle the class average reached 73.46 and in the second cycle the average value of the class increased to 79.62. Not only did the grade average increase, but classical completeness also increased. In the first cycle of classical completeness was 57.69%, then in the second cycle classical completeness increased again to 88.46%. Based on the results of this study, it can be concluded that the application of the type cooperative learning model to Jigsaw Social Studies subjects in Class VII of SMPN 1 Batu Brak can improve student learning outcomes.